Socialization of the Level of Public Awareness and Knowledge about the Benefits of Kombucha Tea in Overcoming Sleep Paralysis During the COVID-19 Pandemic - Yuneka Saristiana; Fendy Prasetyawan; Chadra Arifin; Widhi Astutik; Wahyu Ariawan; Achmad Wahdi (Abdimas Paspama, 2023)
The COVID-19 pandemic has profoundly impacted global public health, prompting a heightened focus on both physical and mental well-being worldwide. In this uncertain landscape, sleep paralysis has emerged as a notable health concern, characterized by the inability to move or speak upon waking or falling asleep, often accompanied by distressing hallucinations. With stress levels on the rise during the pandemic, cases of sleep paralysis have shown an upward trend. Conversely, probiotic beverages like kombucha tea have garnered attention for their potential health benefits, including digestive improvement, enhanced energy levels, and better sleep quality. Despite these benefits, public awareness regarding kombucha tea's efficacy in addressing sleep paralysis remains limited.To address this knowledge gap, a community service program has been developed to educate the public about kombucha tea's potential in managing sleep paralysis amidst the COVID-19 pandemic. The program involves collaboration with local communities, health institutions, and experts in mental health and nutrition. Scheduled for January 2021, the program will be executed across various locations, engaging community members and fostering dialogue on sleep health and nutrition. Preliminary results indicate a significant improvement in public understanding of sleep paralysis and kombucha tea benefits post-program. Participants exhibited heightened awareness of symptoms, causes, and treatment options for sleep paralysis, as well as a better grasp of kombucha tea's health advantages. Practical workshops on kombucha tea preparation garnered considerable interest, signaling a potential shift towards healthier lifestyle choices among participants.